Assessment of Hydropower Potential in the Upper Indus Basin: A Geographic Information System-Based Multi-Criteria Decision Analysis for Sustainable Water Resources in Pakistan - Asim Qayyum Butt; Donghui Shangguan; Muhammad Waseem; Adnan Abbas; Abhishek Banerjee; Nilesh Yadav (Resources)
The development of hydropower projects is crucial to addressing Pakistan’s ongoing energy and financial crises. Despite the country’s abundant hydropower resources, particularly in the northern regions, these have not been adequately explored, while energy consumption and supply issues have persisted for the past two decades. Focusing on Sustainable Development Goal (SDG-7): “Ensure access to affordable, reliable, sustainable, and modern energy”, this study aimed to assess the hydropower potential at suitable sites in the Upper Indus Basin (Pakistan) by integrating Geographic Information Systems (GIS) and Multi-Criteria Decision Analysis (MCDM). This study not only focused on estimating hydropower but also considered the environmental constraints at all sites by using the multi-criteria decision-making (MCDM) tool, which used the location and constraint criteria, along with benefit and cost criteria. The methodology combines technical evaluations (head and discharge) with environmental constraints to prioritize sustainable hydropower development. Key findings identify sites 17, 15, 16, 5, and 6 as the most promising locations, balancing energy generation with minimal environmental impact. This study provides a replicable framework for policymakers to harness hydropower resources responsibly, contributing to Pakistan’s energy security and aligning with global Sustainable Development Goals. This approach not only bridges the gap between technical feasibility and environmental sustainability but also offers a model for other regions facing similar energy challenges.